Determinant Analysis of Customer’s Decision Choosing KJKS Binama Semarang - Isti’anatuz Zumaroh , Hidayat (LP3M STITNU Al Hikmah Mojokerto, 2020)
Abstract : This study aims to analyze the factors that influence customer decisions in choosing the services of Binama Sharia Semarang. The factors influence the customer’s decisions in choosing the Sharia binama financial services cooperative (KJKS Binama) Semarang are the profit sharing system variables, promotional activities, services, administrative requirements, and product knowledge, on the decisions of cooperative members in choosing the KJKS Binama. This study uses quantitative methods and the data process uses SPSS. The data collection techniques uses purposive sampling technique. The sample is 40 members of sharia binama cooperatives. The analysis technique uses multiple linier regression analysis. Based on the results of research conducted is the variables of promotional activities, service and administrative requirements have a positive and significant effect on the decisions of cooperative members in taking the financing of KJKS Binama. While, the variables profit sharing system and product knowledge have positive and not significant effects. Based on the results, the customer's decision to take financing can be explained by the five variables: profit sharing system, promotional activities, services, administrative requirements, and product knowledge, with an R2 value is 0.653. Statistically, 65.3% the customer decisions of KJKS Binama customers are influenced by promotional activities, services and administrative requirements, while the remaining is 23.4 %, influenced by other variables outside of the model. Key word : Customer’s decision, Determinant, Binama Sharia.